Identification of Thalassemia Carrier in Anemic Pregnant Women at Puskesmas Kertapati Palembang: Comparison of Five Erythrocyte Indices - Mitayani Purwoko; Eriko Erenkwot (Universitas Muhammadiyah Surabaya, 2021)
Anemia is a condition that is almost always found in pregnancy. Although a program of Fe tablets has been introduced during pregnancy, the prevalence of anemia during pregnancy is still high. This situation maybe caused by another risk factor of anemia such as Thalassemia. This study was aimed to investigate the presence of carrier Thalassemia in pregnant women at the Puskesmas Kertapati, Palembang, South Sumatera using erythrocyte indices. This was a cross-sectional study with a sample size of 68 subjects, taken by purposive sampling technique. Hemoglobin level of all subjects was measured by Easy touch GCHb and confirmed by Sysmex K21. Differences of hemoglobin between Easy Touch GCHb and Sysmex K21 were analyzed by impaired t-test used SPSS program. Other data were analyzed using descriptive statistic.The mean hemoglobin levels in subjects were 10.7 g/dl. There were 68 subjects have anemia according to Easy Touch GCHb but only 30 subjects that confirmed positive anemia by Sysmex KX 21. T-test result gavep value <0.05 that isconsidered there was a statistically significant difference between Easy Touch GCHb and Sysmex KX 21 results(p=0.001). Calculations using the England-Fraser index, Mentzer, Sirdah, and Srivastava indicate that none of the research subjects had thalassemia carrier status.